Enhancing the accessibility of science at The Lancet with native language abstracts - Christopher H. Wortley (European Science Editing)
Today, 98% of peer-reviewed scientific publishing is in English, which is also the official language of most scientific events and international academic journals. UNESCO, through its Recommendation on Open Science, has called on scientific institutions to foster multilingualism in the practice of science, in scientific publications, and in academic communications. At The Lancet, we recognize the need to provide more equitable and inclusive access to scientific knowledge by providing abstracts translated into relevant languages. Following a pilot, a workflow for abstract translation was devised. I present here details of our abstract translation procedure and rollout.